Pandemic Panic: Examining the Associations between Transformational versus Servant Leadership on In-Role Performance and Burnout in the Context of the COVID-19 Pandemic - Frech, Alison (My University, 2021)
The COVID-19 pandemic fundamentally altered the way people live and work. Organizations were forced to adjust to an unprecedented event, and in doing so, relied on leaders to help their followers navigate this external organizational crisis. This thesis explored two styles of leadership, transformational and servant, and their relationships to follower burnout and in-role performance. Additionally, the mediating role of self-determination theory was investigated to understand how the fulfillment of follower needs may be associated with burnout and in-role performance. Relatedness, one component of self-determination theory, was hypothesized to have the strongest relationship with both burnout and performance. Finally, the thesis proposed that servant leadership would be a better predictor of the two follower outcomes examined than transformational leadership. A total of 159 participants provided usable data from the online questionnaire. Results indicated both leadership styles were related to reduced burnout but had little association with performance. Additionally, the relationship between leadership style and self-determination theory and the relationship between self-determination theory and follower outcomes was supported. Self-determination theory as a mediator for both leadership styles and both follower outcomes was supported but relatedness as the strongest relationship with follower outcomes was not supported. Finally, the proposed model with servant leadership was found to explain more variance in burnout and in-role performance. Limitations and directions for future research are suggested. The implication for managers is that the servant leadership style might be a successful avenue for leadership in a crisis situation.
Keywords: Leadership; COVID-19; Self-determination theory